2022
DOI: 10.1111/ene.15537
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of exosomal α‐synuclein between Parkinson's disease and probable rapid eye movement sleep behavior disorder

Abstract: Background and purpose The insidious onset of Parkinson's disease (PD) makes early diagnosis difficult. Notably, idiopathic rapid eye movement sleep behavior disorder (iRBD) was reported as a prodrome of PD, which may represent a breakthrough for the early diagnosis of PD. However, currently there is no reliable biomarker for PD diagnosis. Considering that α‐synuclein (α‐Syn) and neuroinflammation are known to develop prior to the onset of clinical symptoms in PD, it was hypothesized that plasma total exosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Our results also demonstrated that ASC levels positively correlate with α‑synuclein pathology as the disease progresses, accompanied by an increase in the number of ASC specks. This finding was consistent with what we observed when quantifying the levels of these two proteins in plasma exosomes from PD patients [ 61 ], suggesting that ASC protein may be involved in the propagation of inflammasome-involved pathology triggered by PFFs.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also demonstrated that ASC levels positively correlate with α‑synuclein pathology as the disease progresses, accompanied by an increase in the number of ASC specks. This finding was consistent with what we observed when quantifying the levels of these two proteins in plasma exosomes from PD patients [ 61 ], suggesting that ASC protein may be involved in the propagation of inflammasome-involved pathology triggered by PFFs.…”
Section: Discussionsupporting
confidence: 92%
“…Comparison of the hierarchical bivariate SROC (Fig. 4A) obtained from studies using plasma (11,34,35,36,42,43) or serum (26, 27, 28, 38, 39, 40, 41) also suggested that the studies using serum had, on average, slightly better accuracy, though there was a decent overlap in the con dence intervals of both models. It should also be noted that out of the seven studies using serum, three (27,28,39) and two (40,41), respectively, originated from the same research group while all studies from plasma originated from unique research groups, suggesting a potential overlap in methodologies which may in uence the results.…”
Section: Pd Vs Control: Analysis By Medium and Antibody Clonementioning
confidence: 92%
“…Thirteen studies have attempted to differentiate patients with PD from HCs using biomarkers in nEVs (11,26,27,28,34,35,36,38,39,40,41,42,43) and/or oEVs (40,41). The AUC ranged between 0.61-0.89 with the highest AUC obtained in 2021 by Jiang et al (27), while the sensitivity (Fig.…”
Section: Insert Table 2 Here Pd Vs Controlmentioning
confidence: 99%
See 2 more Smart Citations